2018
DOI: 10.1002/jsfa.9278
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of wine‐based marination of strip steaks prior to roasting: inhibition of protein oxidation and impact on sensory properties

Abstract: Hence, marination may be a feasible means to alleviate the potential negative effects that oxidative reactions cause to meat proteins, improve beef quality, and diversify beef cuts into a variety of safer and more flavored meat products. Among wines, ISA appeared to be most promising in terms of antioxidant protection; however, the limited consumer acceptance of steaks treated with this wine may be regarded as a drawback to be sorted out in future studies. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
(113 reference statements)
0
10
0
Order By: Relevance
“…In recent years, sound scientific evidences from studies in experimental animals have contributed to identify the precise pathological mechanisms of dietary protein oxidation products. Most of these advances have been made on oxidized tyrosine, commonly found in processed muscle foods and red meat digests (Arcanjo, Ventanas, González‐Mohíno, Madruga, & Estévez, ; Rombouts et al., ; Soladoye et al., ). Dietary tyrosine oxidation products (dityrosines being the most abundant) have been found to reach, accumulate, and display pathological effects on target organs (Figure ).…”
Section: Pathogenesis Of Dietary Protein Oxidation: Recent Advancesmentioning
confidence: 99%
“…In recent years, sound scientific evidences from studies in experimental animals have contributed to identify the precise pathological mechanisms of dietary protein oxidation products. Most of these advances have been made on oxidized tyrosine, commonly found in processed muscle foods and red meat digests (Arcanjo, Ventanas, González‐Mohíno, Madruga, & Estévez, ; Rombouts et al., ; Soladoye et al., ). Dietary tyrosine oxidation products (dityrosines being the most abundant) have been found to reach, accumulate, and display pathological effects on target organs (Figure ).…”
Section: Pathogenesis Of Dietary Protein Oxidation: Recent Advancesmentioning
confidence: 99%
“…However, most studies do not report a digest pretreat of samples. Arcanjo et al (2019) and Ozyurt and Otles (2020) used meat homogenates (1:10 w/v) prepared with 100 nM Na 3 PO 4 buffer and 8 M urea, which were filtered and detected. A variety of different buffers are used.…”
Section: Fluorescence Spectrometrymentioning
confidence: 99%
“…Furthermore, the slit width is selected according to the state of the sample. Arcanjo et al (2019) reported a slit width of 10 mm for excitation and emission, while Wang et al (2020) and Feng et al (2015) reported excitation and emission slit widths of 5 mm. Fluorescence spectroscopy is one of the most used methods by researchers.…”
Section: Fluorescence Spectrometrymentioning
confidence: 99%
“…The oxidative deterioration of lipid and protein is a major concern for food technologists due to the loss of sensory quality associated with those processes. Several studies have demonstrated that lipid and protein oxidative processes cause flavour, texture and colour deterioration in meat systems (Smaoui et al ., , ; Arcanjo et al ., ). Equally, it is well known that the growth of several pathogenic bacteria and oxidative reactions affect the shelf life and overall quality of meat (Blanco et al ., ; Laranjo et al ., ).…”
Section: Introductionmentioning
confidence: 98%